Money capital: New monetary principles for a more prosperous society - Bolton, Patrick; huang, Haizhou (Princeton Princeton University Press, 2024)
A conventional economic theory, monetarism, holds that inflation is a monetary phenomenon driven by changes in the supply of money. Yet recent experience$1 (Bincluding the aftermath of the financial crisis of 2008 and the economic development of China$1 (Bcontradicts this basic prediction. In this book, leading economists Patrick Bolton and Haizhou Huang offer a novel perspective, viewing monetary economics through the lens of corporate finance. They propose a rich theory of money supply where money can be seen as the equity capital of a nation, playing a similar role as stocks for a company. This innovative framework integrates the real and monetary sides of the economy, with a banking sector and debt at its core.s